Rethinking disability : bodies, senses, and things - Schillmeier, Michael W. J. (Routledge studies in science, technology and society, 2010)
Offers book-length analysis of disability through the lens of Science and Technology Studies (STS). This book is useful to practicing social service workers and readers in the fields of disability studies, sociology of the body/senses, medical sociology and STS.